Using hydrogen and ammonia for renewable energy storage: A geographically comprehensive techno-economic study - Palys, Matthew J.; Daoutidis, Prodromos (Computers & chemical engineering, 2020)
Highlights•Hydrogen- and ammonia-based energy storage systems for renewable-only energy supply.•Optimal combined capacity planning and scheduling to determine system investment and operation.•Consecutive temporal clustering to efficiently aggregate renewable generation and demand data.•Ammonia suitable for renewable energy storage throughout the United States. Hydrogen and, more recently, ammonia have received worldwide attention as energy storage media. In this work we investigate the economics of using each of these chemicals as well as the two in combination for islanded renewable energy supply systems in 15 American cities representing different climate regions throughout the country. We use an optimal combined capacity planning and scheduling model which minimizes the levelized cost of energy (LCOE) by determining optimal unit selection and size along with unit commitments, production rates, and storage inventories for each period of system operation. These periods are aggregated from full year hourly resolution data via a consecutive temporal clustering algorithm. Ammonia is generally more economical than hydrogen as a single method of energy storage. Additionally, systems which use both hydrogen and ammonia outperform those which use only one storage option and have LCOE between $0.17/kWh and $0.28/kWh, including full investment in renewable generation infrastructure.